Analysis of an open nucleus breeding programme for Djallonke sheep in the Ivory Coast. 1. Examination of non-genetic factors - Yapi-Gnoare, C.V.; Oya, A.; Rege, J.E.O.; Dagnogo, B. (Cambridge University Press, 1997)
Data on Dajllonke sheep collected from 1983 through 1992 on 29 participating farms of an open nucleus improvement programme and from the nucleus were analysed. Initial on-farm records on 14342 lambs and on-station records on 2551 ram lambs were edited down to 6605 for birth weight (BWT), 5857 for pre-selection (birth to 80 days) average daily gain (PSADG), 10417 for 80-day weight (WT80), 13054 for lamb survival at pre-selection, 1978 for 180 (WT180) and 849 for 365 (WT365) day weights. Year of birth, sire line, flock, month and season of birth had significant (at least P<0.05) effects on both on-farm and on-station weights and on lamb survival. Trait means were 2.2 (s.e. 0.02) kg for BWT, 69.6 (s.e. 1.26) g/day for PSADG, 9.1 (s.e. 0.05) kg for WT80, 19.7 (s.e. 0.24) kg for WT180 and 31.8 (s.e. 0.45) kg for WT365. Mean survival was 90 (s.e. 0.9) percent. Single lambs were heavier at birth and at 80 days of age, grew faster to 80 days and were about 200 and 500 g heavier at 180 and 365 days respectively than multiple lambs. There was a large variation between flocks: flock means for WT80 varied from 6.4 to 12.0 kg (CV 0.21), with smaller flocks having generally the lowest means. Lambs born in the hot-rainy season had the heaviest 180- and 365-day weights. Lambs born during the cool months of July to October had the lowest survival rate. Multiplicative factors were found to be more appropriate for adjusting on-farm recordes for type of birth, management level, birth date, season of birth and ewe parity than additive adjustment factors.